Investigating the Effect of Different Levels of Butyric Acid Glycerides and Clove Oil on Growth Performance, Blood Parameters and Tibia Bone Characteristics of Broiler Chickens - Seyyedeh azam khatami; Mir Daryoush Shakouri; Nemat Hedayat Evrigh (پژوهشهای علوم دامی ایران)
Introduction: Today, livestock and poultry health in the advanced production system is the main challenge affecting human health and the global economy. For years, antibiotics have been widely used as growth promoters to stabilize the microbial population of the digestive tract and improve performance. However, scientific evidence suggests that the massive use of these compounds has led to increased problem of antibiotic resistance and presence of antibiotics residues in feed and compromises human and animal health. Hence, there is a growing need to find effective alternatives to control infectious diseases and limit the spread of resistant bacteria.Organic acids are an alternative to antibiotics in poultry diets. These are improving the immune system of broilers by acidifying the gastrointestinal tract and improving the intestinal microflora. Coating of organic acids prevents their dissociation and digestion in the stomach so that the biological effect of organic acids reaches the distal parts of the gastrointestinal tract and is effective in intestinal microflora and mucosal morphology. Also, Essential oils are volatile oil compounds that are produced as secondary metabolites by plants. Essential oils extracted from plants have anti-bacterial, anti-viral, anti-fungal, antioxidant activities as well as immune-modulating effects, reducing blood fat and stimulating the digestive system of poultry. Organic acids can complete the effect of essential oils through synergism antibacterial and bactericidal activities. Therefore, the present study was designed to investigate the effect of different levels of butyric acid glycerides and clove oil on growth performance, blood parameters and tibia bone characteristics of broiler chickens. Material and Methods: A total of 300 male and female broilers (Ross 308) with a completely randomized design with a 2 × 3 factorial arrangement, two levels of butyric acid glycerides (0 and 0.2 %) and three levels of clove oil (0, 500 and 1000 mg/kg) were used. Each of the six dietary treatments was fed to five replicate pens of 10 birds each from 0 to 42 days of age. Body weight gain, feed intake, feed conversion ratio, weights of immune organs, plasma lipids and physical and mineral characteristics of the tibia were recorded. The collected data were analyzed using SAS software (2003) and using the general linear model (GLM) procedure. The equation of the statistical model of the experiment was according to the relation Yijk = µ + Ai + Bj + (AB)ij + eijk, where Yijk represents the numerical value of each observation, µ is the population mean, Ai is the effect of butyric acid glycerides (0 and 0.2%), Bj was the effect of clove oil (0, 500 and 1000 mg/kg), ij (AB) was the interaction effect of butyric acid glycerides and clove oil, and eijk was the experimental error.Results and Discussion: The results showed that the addition of 0.2% butyric acid glycerides in the diet of broiler chickens reduced feed intake, body weight and daily weight gain compared to the control group (P<0.05). Addition of 1000 mg/kg of clove oil in the diet reduced feed intake, body weight, daily weight gain and european production index compared to the control group (P<0.05). Body weight, feed efecioncy, european efficiency factor and feed conversion ratio of broiler chickens were affected by the interaction effect of butyric acid glycerides and clove oil (P<0.05). The addition of different levels of clove oil with and without butyric acid glycerides in the broiler diet reduced cholesterol and LDL concentration compared to the control group (P<0.05). But the concentration of triglyceride, HDL and VLDL were not affected by the experimental treatments. The interaction effect of clove oil and butyric acid glycerides did not affect the weight of bursa of fabricius, thymus and spleen of broiler chickens. The amount of calcium, phosphorus and ash of tibia bone was significantly affected by butyric acid glycerides. Also, the length of the tibia of broiler chickens was affected by the clove oil and the interaction effect of butyric acid glycerides and clove oil (p<0.05).Conclusion: In general, no synergistic effect was observed between butyric acid glycerides and clove oil on growth performance of chickens. Although the use of 0.2% butyric acid glycerides and 1000 mg/kg clove oil led to a decrease in the weight gain of chickens by reducing feed intake, but the addition of butyric acid glycerides caused an increase in the concentration of phosphorus, calcium and ash in the tibia bone of broiler chickens.